Influência dos polimorfismos Taql e Bsml do gene do receptor de vitamina D no surgimento de infecção, tempo de internação e mortalidade em pacientes queimados - Nogueira, Gláucia Regina [UNESP] (2015)
Introduction: Some studies showed that the inflammatory process was related with severe burn injury. Thus, strategies for modulation of inflammatory response are of great interest. In the last years, vitamin D received attention due to its anti-inflammatory and immunomodulatory actions. Most of the actions of vitamin D are through its nuclear receptor (VDR). Recent studies showed that VDR gene polymorphisms could influence vitamin D response. Objective: The objective of this study is to evaluate the association of Taql and Bsml polymorphisms of VDR gene with length of hospital stay, infection development and mortality in burn patients. Methods: We prospectively evaluated burn patients, over the age of 18 years, admitted to the Burn Unit of Hospital Estadual Bauru. The patients were included from January 2013 to January 2014, after signing the written informed consent. Upon admission demographical and clinical data were recorded. Blood sample was collected for biochemical analysis, measure of serum 25(OH) vitamin D3 concentration, and Taql and Bsml polymorphisms determination. The patients were followed during hospital admission, and length of hospital stay, infection development and mortality were recorded. For association between length of hospital stay and VDR polymorphisms we used uni and multivariate linear regressions. For association between polymorphisms and infection development and mortality, uni and multiple logistic regressions were performed. Significance level was 5%. Results: We evaluated 87 patients, however 7 were excluded due to technical problems with VDR polymorphism evaluation. Thus, 80 patients were studied. Considering these patients 60% were male, and average age was 42.5 ± 16.1 years. Regarding the cause of burn 47.5% were caused by fire, 33,7% due to hot liquids, 15% caused by electricity and 3.8% due to other causes. The median of burn surface area was 8.0 (3.0-18.8)% and 47.5% were treated in intensive care ...